Quran Memorization Technologies and Methods: Literature Review - Kholid Haryono; Rian Adam Rajagede; Muhammad Ulil Albab Surya Negara (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
The application of the Qur'an for the memorizers in adding and maintaining their memorization continues to grow in number. No less than 200 digital Qur'an applications are available on mobile application providers. In addition, publications on the topic of the digital Qur'an in the last ten years have also increased. Through these applications and publications, it is an opportunity to find patterns and knowledge about current topics and features. Through this knowledge, it is hoped that it can be a recommendation for a better form of digital Al-Qur'an application system, especially providing features that affect increasing the ease and quality of memorizing the Qur'an. This paper aims to explore the application of the Qur'an specifically for memorizing and papers on the topic to provide these recommendations. The method used to get the paper using PRISMA. While the applications being reviewed are taken from the AppStore. As a result, 31 papers were reviewed and 12 main applications regarding the Qur'an for memorization were obtained. Through the answers to each research question, it can be used by subsequent researchers as well as by system developers in developing Al-Qur'an products for better memorization of tense.